2018
DOI: 10.1051/matecconf/201714201005
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Activated Carbons from Waste External Thermal-Insulating Phenolic Foam Boards

Abstract: Abstract. Activated carbons (ACs) were prepared by steam physical activation or KOH chemical activation with the waste external thermal-insulating phenolic foam board as the raw material. The Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) specific area, pore-size distribution and iodine value were used to characterize the properties of ACs. AC-1(with the method of KOH chemical activation) has the iodine value of 2300mg/g, BET specific area of 1293 m 2 g -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the production of activated carbon has been achieved with various types of starting materials (precursors), either from plant sources (i.e., wood, coconut shell, rice husk) or mineral sources (i.e., coal, pet cokes, asphaltene). 2 Nevertheless, to date, most of the existing studies have been limited to using activated carbon synthesized from a single feedstock. 3 Kaghazchi et al 4 reported that current practices are undesirable because each of the carbonaceous feedstock has its own limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the production of activated carbon has been achieved with various types of starting materials (precursors), either from plant sources (i.e., wood, coconut shell, rice husk) or mineral sources (i.e., coal, pet cokes, asphaltene). 2 Nevertheless, to date, most of the existing studies have been limited to using activated carbon synthesized from a single feedstock. 3 Kaghazchi et al 4 reported that current practices are undesirable because each of the carbonaceous feedstock has its own limitations.…”
Section: Introductionmentioning
confidence: 99%
“…reported that its global demand can reached up to 2.2 million metric tons by 2022, with an increasing rate of 4.2% per annum . Therefore, the production of activated carbon has been achieved with various types of starting materials (precursors), either from plant sources (i.e., wood, coconut shell, rice husk) or mineral sources (i.e., coal, pet cokes, asphaltene) 2 . Nevertheless, to date, most of the existing studies have been limited to using activated carbon synthesized from a single feedstock 3 .…”
Section: Introductionmentioning
confidence: 99%